The S100 protein family in bladder cancer: mechanisms, clinical value, and targeted therapeutic prospects - Zhang, Lihao; Yang, Gang; Huang, Lige; Deng, Aijia; Ao, Mengxin; Li, Jiabing (Frontiers in Oncology, 2025)
BackgroundBladder cancer (BC) is a highly heterogeneous malignancy with limited molecular biomarkers and therapeutic targets. The S100 protein family, a group of calcium-binding proteins, has emerged as a crucial regulator in cancer development. However, their mechanistic roles and clinical significance in BC remain underexplored.MethodsThis review summarizes the current understanding of the expression patterns, biological functions, and signaling mechanisms of key S100 family members in BC, integrating data from transcriptomic studies, public databases (The Cancer Genome Atlas Program, Gene Expression Omnibus), and recent preclinical research.ResultsS100 family members such as S100A8, S100A9, S100A13, and S100A6 are upregulated in advanced BC and are associated with tumor progression, immune suppression, and poor prognosis. In contrast, S100C exhibits tumor-suppressive properties. Mechanistically, S100 proteins promote epithelial-mesenchymal transition, angiogenesis, and immune evasion by activating receptor for advanced glycation end products(RAGE) and toll-like receptor 4 (TLR4)-mediated signaling pathways. Emerging evidence supports the development of S100-targeted therapeutics including small molecules, monoclonal antibodies, and RAGE inhibitors.ConclusionS100 proteins represent promising biomarkers and therapeutic targets in BC. Integrating S100-based profiling into clinical practice may improve molecular classification, prognostication, and personalized treatment. Future efforts should focus on resolving protein redundancy, validating context-specific functions, and advancing drug development for clinical translation.